Role of α2-adrenoceptors in the lateral parabrachial nucleus in the control of body fluid homeostasis - Andrade, C. A.F. [UNESP]; Andrade-Franzé, G. M.F. [UNESP]; De Paula, P. M. [UNESP]; De Luca, L. A. [UNESP]; Menani, J. V. [UNESP] (FapUNIFESP (SciELO), 2014)
Central α2-adrenoceptors and the pontine lateral parabrachial nucleus (LPBN) are involved in the control of sodium and water intake. Bilateral injections of moxonidine (α2-adrenergic/imidazoline receptor agonist) or noradrenaline into the LPBN strongly increases 0.3 M NaCl intake induced by a combined treatment of furosemide plus captopril. Injection of moxonidine into the LPBN also increases hypertonic NaCl and water intake and reduces oxytocin secretion, urinary sodium, and water excreted by cell-dehydrated rats, causing a positive sodium and water balance, which suggests that moxonidine injected into the LPBN deactivates mechanisms that restrain body fluid volume expansion. Pretreatment with specific α2-adrenoceptor antagonists injected into the LPBN abolishes the behavioral and renal effects of moxonidine or noradrenaline injected into the same area, suggesting that these effects depend on activation of LPBN α2-adrenoceptors. In fluid-depleted rats, the palatability of sodium is reduced by ingestion of hypertonic NaCl, limiting intake. However, in rats treated with moxonidine injected into the LPBN, the NaCl palatability remains high, even after ingestion of significant amounts of 0.3 M NaCl. The changes in behavioral and renal responses produced by activation of α2-adrenoceptors in the LPBN are probably a consequence of reduction of oxytocin secretion and blockade of inhibitory signals that affect sodium palatability. In this review, a model is proposed to show how activation of α2-adrenoceptors in the LPBN may affect palatability and, consequently, ingestion of sodium as well as renal sodium excretion.
Keywords: Hindbrain; Natriuresis; Parabrachial nucleus; Sodium; Taste; Thirst